Mobile application utilizing 2D animation to learn animals stories in Quran in multi languages - Yousef A. Baker, El-Ebiary; Elsayed Mohamed Salem, Salem Elawadi; Syarilla Iryani, A. Saany (2020)
This portable utility development project "the cellular mastering application of tutorial relate to animal's name in holy Quran" is constructed up its expects to encourage its usage and in accordance with the prevailing gradually complex innovation. in creating this mobile cell phone software. a few destinations and targets are targeted on. the fundamental goals are to break down the focal points and disadvantages handy on present cellular telephone packages, structuring an advanced and step by step attractive interface from the beyond versatile gaining knowledge of utility and growing alluring and possible transportable getting to know utility programming to help children with thinking about something new. additionally, this portable mastering application that consist of special blended media components in conjunction with content material in English, Arabic and Malay, video, sound and motion. a number of the proposals endorsed to improve and improve this utility is that the interest brought have to be an increasing number of progressive and alluring for the assessment of kids and the catches made to make intelligence should be more easy to recognize.